TARIQ RAMADAN'S INTERPRETATION OF THE REALITY OF MUSLIM MINORITIES IN THE WEST - Nasrullah, Nasrullah (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2024)
The issue of minorities and the majority of Muslims is still an issue in the midst of socio-religious relations in world society. Especially between Muslims and Western society. Misunderstandings often occur and even lead to hostility, because a balanced understanding has not yet been reached. Tariq Ramadan, as a scholar and Muslim citizen in the West, reminded Western citizens that they need to understand Islam. Likewise, Muslim citizens must also understand things that occur in the Western cultural system which is based on modernism, democracy and rationality. The prerequisite he offered was that, based on his interpretation of the reality of Muslims in the West, it was necessary to encourage attitudes and changes in views, that Islam could also live in the dimensions of modernity and democracy in coexistence in the West and proclaimed that Islam is a religion of love for humanity and peace.